Review of display technologies and market - Ong, Teck Soon. (2008)
The purpose of this report is to look into the trend of display technologies. The focal point of this study is to find out how flat-panel displays are steadily eating into the market share of conventional Cathode Ray Tubes (CRTs) and different flat-panel display technologies are making advance. This report delves into CRTs and Flat-Panel Displays from their early beginnings to the present state of art covering the historical perspective, theory of operations and specific applications of the display technologies.